ELEMENTY ORGANIZACYJNE KATECHEZY PRZYGOTOWUJĄCEJ MŁODZIEŻ DO SAKRAMENTU BIERZMOWANIA W POLSCE I W NIEMCZECH - Kaczmarek, Robert (Studia Katechetyczne, 2016)
The religious education which prepares for Confirmation should be incessantly renewed. It results from the unprecedented pace of civilizational changes, on which the youth are exposed. They need reinforcement which the Sacrament of Confirmation brings. It also constitutes the unusual chance in the process of faith of the young man. Seeking the optimal model of the religious education for Confirmation, and more widely a youth chaplaincy, is an expression of care of the young man. Using mutual experience and learning from each other can bring new and valuable inspiration. One can see it on the example of compared organizational elements of the religious education which prepares for Confirmation in Poland and in Germany. Without their proper forming even the best selected content and methods of the transmission will not be able to bring full fruits.